TANGGUNG JAWAB PERUSAHAAN UMUM DAERAH (PERUMDA) AIR MINUM TIRTA MUARO JAMBI TERHADAP KERUGIAN KONSUMEN DALAM PELAYANAN AIR MINUM DI KABUPATEN MUARO JAMBI - Heni Girlbet Silalahi; Pahlefi Pahlefi; Ageng Triganda Sayuti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims: 1) To find out and analyze the implementation of the responsibility of the Perumda Air Minum Tirta Muaro Jambi towards the fulfillment of consumer rights in drinking water services, 2) To find out and analyze the dispute resolution efforts carried out by Perumda Air Minum Tirta Muaro Jambi on the losses suffered by consumers. The method used in this research is the empirical juridical method. This research is descriptive, the sampling procedure is purposive sampling. The research results obtained are 1). The responsibility of the Tirta Muaro Jambi Drinking Water Perumda is an absolute responsibility (strict product liability) but in its implementation Perumda Air Minum Tirta Muaro Jambi not yet absolutely responsible for fulfilling consumer rights in drinking water services. There are still 115 complaints that have not been responded to or 46% of the 246 Perumda Air Minum Tirta Muaro Jambi customers who reported the complaint. 2) Perumda Air Minum Tirta Muaro Jambi has attempted to settle consumer demands for negligence by Perumda Air Minum Tirta Muaro Jambi but not optimal. Efforts made by Perumda Air Minum Tirta Muaro Jambi: a. Conduct site inspections in case of pipe leaks; b. Find out the cause of expensive payments; c. Replace the customer's water meter if there is damage due to negligence of the Perumda Air Minum Tirta Muaro Jambi. As well as efforts to resolve disputes that have existed at Perumda Air Minum Tirta Muaro Jambi are by way of peace or negotiation.